Evaluation of Serum-Derived Bovine Immunoglobulin Protein Isolate in Subjects With Decompensated Cirrhosis With Ascites - Stotts, Matthew J; Cheung, Amanda; Hammami, Muhammad B; Westrich, David J; Anderson, Eric; Counts, Lauren; Befeler, Alex S; Di Bisceglie, Adrian M; Prather, Charlene (Curēus (Palo Alto, CA), 2021)
Background Bacterial translocation plays a pivotal role in the natural course of cirrhosis and its complications. Serum-derived bovine immunoglobulin (SBI) is an oral medical food that has been shown to both reduce inflammation in the intestines and neutralize bacteria. It represents a unique intervention that has not been studied in this population. Methodology We conducted a prospective open-label trial with an eight-week treatment phase of SBI. Individuals were assessed using lactulose breath testing, serum markers for enterocyte damage and bacterial translocation, and the Chronic Liver Disease Questionnaire (CLDQ) prior to and after completion of the treatment phase. Results We evaluated nine patients with a diagnosis of decompensated cirrhosis with ascites. Subjects had a mean Model for End-Stage Liver Disease (MELD) score of 11.6 ± 3.0 and were not taking lactulose or antibiotics. All subjects tolerated SBI well with no significant adverse events or changes to any of the six domains of the CLDQ. Laboratory tests including liver tests and MELD score remained stable over the course of treatment. There were no significant changes in the rates of small intestinal bacterial overgrowth (55.6% vs 55.6%, p = 1.00) or serum levels of lipopolysaccharide-binding protein, intestinal fatty acid-binding protein, or soluble CD14 (p-values 0.883, 0.765, and 0.748, respectively) when comparing values prior to and immediately after treatment. Conclusions No adverse events or significant changes to the quality of life were detected while on treatment. There were no statistically significant differences in our outcomes when comparing individuals before and after treatment in this small prospective proof-of-concept pilot study. Further prospective randomized studies could be beneficial.Background Bacterial translocation plays a pivotal role in the natural course of cirrhosis and its complications. Serum-derived bovine immunoglobulin (SBI) is an oral medical food that has been shown to both reduce inflammation in the intestines and neutralize bacteria. It represents a unique intervention that has not been studied in this population. Methodology We conducted a prospective open-label trial with an eight-week treatment phase of SBI. Individuals were assessed using lactulose breath testing, serum markers for enterocyte damage and bacterial translocation, and the Chronic Liver Disease Questionnaire (CLDQ) prior to and after completion of the treatment phase. Results We evaluated nine patients with a diagnosis of decompensated cirrhosis with ascites. Subjects had a mean Model for End-Stage Liver Disease (MELD) score of 11.6 ± 3.0 and were not taking lactulose or antibiotics. All subjects tolerated SBI well with no significant adverse events or changes to any of the six domains of the CLDQ. Laboratory tests including liver tests and MELD score remained stable over the course of treatment. There were no significant changes in the rates of small intestinal bacterial overgrowth (55.6% vs 55.6%, p = 1.00) or serum levels of lipopolysaccharide-binding protein, intestinal fatty acid-binding protein, or soluble CD14 (p-values 0.883, 0.765, and 0.748, respectively) when comparing values prior to and immediately after treatment. Conclusions No adverse events or significant changes to the quality of life were detected while on treatment. There were no statistically significant differences in our outcomes when comparing individuals before and after treatment in this small prospective proof-of-concept pilot study. Further prospective randomized studies could be beneficial.